2021
DOI: 10.1681/asn.2020101442
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Altered Matrix Signature in Kidney Aging and Disease

Abstract: Background: Accumulation of extracellular matrix in organs and tissues is a feature of both aging and disease. In the kidney, glomerulosclerosis and tubulointerstitial fibrosis accompany the decline in function, which current therapies cannot address, leading to organ failure. Whilst histological and ultrastructural patterns of excess matrix form the basis of human disease classifications, comprehensive molecular resolution of abnormal matrix is lacking. Methods: Using mass spectrometry-based proteomics we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 56 publications
4
59
0
Order By: Relevance
“…We discovered many genes that function to restrict BM collagen IV levels. These collagen IV limiting mechanisms might break down during senescence and disease, as altered collagen IV levels is a hallmark of aging, diabetes, and Alzheimer's disease 19,[64][65][66] . We found the TGFβ pathway and ROBO restrict collagen IV accumulation in C. elegans and zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We discovered many genes that function to restrict BM collagen IV levels. These collagen IV limiting mechanisms might break down during senescence and disease, as altered collagen IV levels is a hallmark of aging, diabetes, and Alzheimer's disease 19,[64][65][66] . We found the TGFβ pathway and ROBO restrict collagen IV accumulation in C. elegans and zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate BM diversity in human tissues, the relative abundance of the BM zone network within proteomic datasets for human kidney 19 , liver 16 , colon 16 , and omentum 32 was ranked (Supplementary table 8). We found a common set of BM zone proteins that were abundant across all tissues, including COL4A1/2, COL6A1/A2/A3, LAMB2/C1, NID1, and HSPG2 (perlecan), and identified proteins with highly variable abundance, such as DCN and TINAG (Fig.…”
Section: Identification Of Tissue-specific Bm Composition Signaturesmentioning
confidence: 99%
“…This may contribute to why ACE inhibitors, which reduce intraglomerular pressure, slow the progression of Alport kidney disease in both mice and human ( 9 11 ). A recent mass-spectroscopy-based proteomics study demonstrated aan overall reduction in basement membrane proteins in glomerular matrix from Alprot mice relative to wild type mice with an overall increase in interstitial matrix proteins ( 12 ). These changes are likely to contribute to the biomechanical prpoperties of the GBM in Alport syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…This method infers protein presence based on the identification of the most abundant peptides in any given sample. Proteomics has revealed that the ECM of any given tissue is made of well over 100 distinct proteins and has allowed the identification of ECM protein signatures characteristic of physiological processes (e.g., development [18], aging [19][20][21][22]) and pathological states (e.g., cardiovascular diseases [23], cancer [24], fibrosis [25][26][27]). However, existing proteomic approaches present limitations.…”
Section: Introductionmentioning
confidence: 99%